2016
DOI: 10.4274/tybdd.52824
|View full text |Cite
|
Sign up to set email alerts
|

Where are We on Organ Donation?

Abstract: Adıyaman Üniversitesi Eğitim ve Araştırma Hastanesi, yoğun bakım ünitesinde beyin ölümü tanısı konulan olguların demografik ve klinik özellikleri retrospektif olarak incelenerek, organ bağışı kabul oranları sunuldu. Gereç ve Yöntem: Hastanemiz yoğun bakım ünitesinde 2008-2014 yılları arasında beyin ölümü tanısı konmuş hastalar retrospektif olarak incelendi. Tüm hastalar; yaş, cinsiyet, beyin ölümü nedeni, kan grubu, organ bağışı kabul ve red nedenleri, kardiyak arrest geçirme ve vazopressin kullanma durumu, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
2
0
3
Order By: Relevance
“…Intracerebral hemorrhage was the most common cause of brain death in our study, similar to the studies by Escudero et al [13] and Pandey et al [3]. However, many studies reported different primary causes of brain death [14-15,19]. The difference in the most common cause of brain death in various studies may be a result of using different classifications for the cause of brain death.…”
Section: Discussionsupporting
confidence: 88%
“…Intracerebral hemorrhage was the most common cause of brain death in our study, similar to the studies by Escudero et al [13] and Pandey et al [3]. However, many studies reported different primary causes of brain death [14-15,19]. The difference in the most common cause of brain death in various studies may be a result of using different classifications for the cause of brain death.…”
Section: Discussionsupporting
confidence: 88%
“…Gender varies between countries in patients diagnosed with brain death. In our study, 52.3% of patients diagnosed with brain death were female gender; studies conducted in our country reported that the majority of those diagnosed with brain death are male sex 7,8,9,10 . Aghighi et al 11 reported from Iran that the rate of brain death in males was 2.1 times that of females and Han et al 12 in a study conducted in South Korea; women were more diagnosed with brain death (65%).…”
Section: Discussionsupporting
confidence: 44%
“…Karasu et al 7 reports that; Of the 79 patients diagnosed with brain death during a 7-year period in Bursa Yüksek İhtisas Training and Research Hospital, 27 (34.2%) of the families gave consent to organ donation, Kıraklı et al 8 in a study conducted for past 2 years in Izmir Tepecik Education and Research Hospital in 48 out of 1759 patients were found to be diagnosed with brain death, and 33 patients (69%) found that their relatives accept organ donation. Uludağ et al 9 reported that 59 patients were diagnosed with brain death between 2008 and 2014 in Adıyaman University Training and Research Hospital, and five patients (8.7%) were donors. Han et al 12 examined 107 cases with brain death and found that the organ donation rate was 58% (n: 62).…”
Section: Discussionmentioning
confidence: 99%
“…Uludağ ve ark. [15] tarafından Adıyaman'daki bir eğitim ve araştırma hastanesinde gerçekleştirilen çalışmada olguların %59.6'sı erkek, %31.5'i A kan grubu bulunmuştur. Hastaneye yatış tanıları açısından incelendiklerinde ise subaraknoid kanama (%42) ve intraserebral hematom (%14) ilk sıralardadır.…”
Section: Gereç Ve Yöntemunclassified